Między unikalnością a uniwersalizmem: obraz bohaterów aborygeńskich. Recepcja australijskiej literatury aborygeńskiej w Polsce - Podemska-Abt, Teresa (Postscriptum Polonistyczne, 2020)
Being a result from the 2008/9 research into interpretation of Aboriginal literature within Polish readerships, the article explores ways in which Indigenous characters are imagined and understood by Polish readers. Also, given that literatures and their characters are usually looked throughout the readers’ schemata and memory scans, it shows the dominant ways in which the Polish readers interpret and communicate with some of those characters.